Emotional intelligence, social intelligence and students’ strategic learning behavior - Praditsang, Mali (2016)
There has been an increase in the enrolment of students in Institution of Higher Education in Thailand. However, retention of students has become a problem for Thai institutions of higher education and especially for Songkla Rajabhat University. While the enrolment of students at Songkhla Rajabhat University is increasing throughout the years, the number of students graduating is drastically decreasing. This study was therefore conducted to examine the level of students’ emotional intelligence, social intelligence and strategic learning behaviour; the influence of emotional and social intelligence on students’ strategic learning behaviour and the role of demographic factors on the relationship between emotional intelligence, social intelligence and strategic learning behaviour. A survey method was used to gathered information from 569 first year students. The questionnaire covers demographic factors, emotional intelligence, social intelligence and strategic learning behavior. The results showed that emotional intelligence (3.80) and social intelligence (3.77) were high while strategic learning behaviour (3.52) was at medium level. It was also revealed that there was no significant on emotional intelligence; social intelligence and strategic learning behavior base on demographic factors. Social intelligence and emotional intelligence were significantly related to strategic learning behaviour. Therefore, this study implies that social and emotional intelligence are important factors to consider in enhancing students’ strategic learning behavior and this will help the lecturers, school administrators, policy makers and the government in designing strategies to enhance graduation rate.